Free ammonia offers algal crop protection from predators in dairy wastewater and ammonium-rich media. (November 2017) - Thomas, Patrick K.; Dunn, Gary P.; Passero, Maxine; Feris, Kevin P.
Graphical abstract: Highlights: Free NH3 concentrations that inhibit rotifers do not affect a model algal species. Exposure time to free NH3 was optimized for algal production and pest control. 6- and 12-h of free NH3 exposure inhibited rotifers with no effect on algae. This approach may provide a sustainable, low-cost algal crop protection strategy. Abstract: Cost-effective methods for protecting crops from grazing organisms like rotifers are needed to reduce the risk of pond crashes in mass algal cultures. We present a novel strategy to optimize the exposure time to free ammonia, via control of media pH, in both defined media and dairy anaerobic digester effluent to suppress rotifers and maintain algal productivity. We tested five different free ammonia exposure times (0, 1, 2, 6, and 12 h) and found a significant nonlinear effect of exposure time (p < 0.0001) but not pH (p > 0.9) on rotifer survival. In both media types, 6–12 h of elevated free ammonia significantly reduced Brachionus plicatilis rotifer survival with no negative effects on Nannochloropsis oculata, while shorter exposure times were insufficient to inhibit rotifers, leading to severe algal culture crashes. These results suggest that algal crops can be protected from rotifers, without productivity loss, by elevating free ammonia for 6 or more hours.